Four-Color Pseudovirus-Based Neutralization Assay: A Rapid Method for Evaluating Neutralizing Antibodies Against Quadrivalent Hand, Foot, and Mouth Disease Vaccine - Fan Gao; Lingjie Xu; Qian Wang; Gang Wang; Mingchen Liu; Lu Li; Qian He; Xuanxuan Zhang; Ying Wang; Qunying Mao; Zhenglun Liang; Tao Wang; et al. (Vaccines)
Background/Objectives: Enterovirus 71 (EV71) and coxsackieviruses A16 (CA16), A10 (CA10), and A6 (CA6) are the primary pathogens that cause hand, foot, and mouth disease (HFMD). Currently, many manufacturers are developing bivalent, trivalent, and tetravalent vaccines that target these antigens. Cell-based neutralization assay (CBNA), the gold standard for detecting neutralizing antibodies (NtAbs), which are used as indicators of HFMD vaccine efficacy, has several limitations. We aimed to develop a novel assay for detecting NtAbs against a quadrivalent HFMD vaccine. Methods: We developed a four-color pseudovirus-based neutralization assay (PBNA), utilizing fluorescent reporter genes, to rapidly evaluate neutralizing antibodies against EV71, CA16, CA10, and CA6 in multivalent vaccines and compared it with CBNA. Results: PBNA could rapidly and simultaneously detect NtAbs against the four serotypes and required lesser amounts of sera compared to CBNA. A good consistency in determining NtAb titers was observed for PBNA and CBNA. Conclusions: PBNA provides a robust tool for evaluating the efficacy of multivalent HFMD vaccines and conducting seroepidemiological studies.